Handbook of proteolytic enzymes - Rawlings, Neil D.; Salvesen, G. (Academic, 2012)
The third edition of the Handbook of Proteolytic Enzymes is a fully revised and updated major reference work in Elsevier's canon. For the first time the Handbook will be available as an online via Elsevier's ScienceDirect platform as well as a three-volume book. The online version will have the enhanced options including online multimedia, cross-referencing capabilities, integrated online delivery and closer integration with the online MEROPS database of peptidases and their inhibitors. This reference work is intended for university libraries, researchers and students, and will be of great.- Resumé vydavatel